Impairments of glutamatergic synaptic transmission in Alzheimer’s disease - Zott, Benedikt; Konnerth, Arthur (Seminars in cell & developmental biology, 2023)
One of the hallmarks of Alzheimer’s disease (AD) is structural cell damage and neuronal death in the brains of affected individuals. As these changes are irreversible, it is important to understand their origins and precursors in order to develop treatment strategies against AD. Here, we review evidence for AD-specific impairments of glutamatergic synaptic transmission by relating evidence from human AD subjects to functional studies in animal models of AD. The emerging picture is that early in the disease, the accumulation of toxic β-amyloid aggregates, particularly dimers and low molecular weight oligomers, disrupts glutamate reuptake, which leads to its extracellular accumulation causing neuronal depolarization. This drives the hyperactivation of neurons and might facilitate neuronal damage and degeneration through glutamate neurotoxicity. •Studies in brain tissue from AD patients provide evidence for the impairment of glutamatergic neurons and circuits in AD.•Experiments in animal models demonstrated Aβ-dependent glutamate accumulation by an inhibition of glutamate reuptake.•Neuronal hyperactivity in early AD stages is caused by the Aβ-dependent accumulation of perisynaptic glutamate.